Problems of writing skill among non-Arabic speakers (Applicable to specialized institutes in the Kingdom of Saudi Arabia) - Mohamed, Gamal Hussaein Gaber; Abedalah, Suliman Yousif Mohammed; Abdelhameed, Saeed Mahmoud Musa (Journal of Educational and Psychological Sciences, 2022)
The purpose of this study to find out the knowledge problems of the Arabic language choice and related to languages ​​other than those specialized in the field of specialized research, in order to reach the types of research and environmental problems, their classification, their ratio, their causes, and the listing of treatments. In order to achieve the objectives of the previous study, the descriptive approach based on analysis as it is an experimental study. He prepared a study of the learners ’questionnaire, and an interview for the professors to find out their views on these problems, and the sample of the study (61) learners from the standard level for teaching the Saudi Arabian language, for teaching the Saudi Arabian language, and (23)) As a teacher, and the most prominent results of the problems were: The application of spelling rules in the skill of writing, the struggle to employ pronouns in all their conditions in the context of writing, and the distinction between long and short movements when practicing writing.
Keywords: writing skill; non-Arabic language learners; education; Saudi Arabia